Politis, V. (2015). The Structure of Enquiry in Plato’s Early Dialogues. Cambridge, Cambridge University Press. - Sabrier, Pauline (Revista Archai, 2015)
Politis, V. (2015). The Structure of Enquiry in Plato’s Early Dialogues. Cambridge, Cambridge University Press.